2020
DOI: 10.1186/s13018-019-1466-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sliding plate technique for coronal shear fractures of the distal humerus

Abstract: Purpose: The purpose of this study is to discuss the surgical strategy, technical feasibility, and clinical efficacy of coronal shear fractures of the distal humerus using the anti-sliding plate technique. Methods: Fifty-two patients (35 males and 17 females) were treated with the anti-sliding plate technique in our hospital from January 2012 to January 2017. The average age of the patients was 40.4 years. They were classified according to the Dubberley classification system and treated with the anti-sliding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
(34 reference statements)
1
19
0
Order By: Relevance
“…The results of our study are in accordance with recent clinical studies that suggest plating as the treatment of choice in those complex fracture patterns [26,31]. Wang et al [31] recently evaluated the safety and efficacy of the fixation of Dubberley type B capitellar and trochlear fractures in a clinical study using posterolateral anatomic plates with support of the distal humerus.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of our study are in accordance with recent clinical studies that suggest plating as the treatment of choice in those complex fracture patterns [26,31]. Wang et al [31] recently evaluated the safety and efficacy of the fixation of Dubberley type B capitellar and trochlear fractures in a clinical study using posterolateral anatomic plates with support of the distal humerus.…”
Section: Discussionsupporting
confidence: 90%
“…Sen et al introduced the concept of additional fracture stabilization using an anterior placed antiglide plate following traditional AO principles by neutralizing shear forces [24]. Song et al [26] recently evaluated the technical feasibility and clinical efficacy of coronal shear fractures of the distal humerus using the anti-sliding plate technique. The authors suggest that the anti-sliding plate technique allows a stable internal fixation of the fracture, which is critical for early mobilization and a good functional outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mini-fragment plate or a one-third tubular plate can be contoured to fit anteriorly and its distal portion is bent approximately 60° at the level of the articular surface of the capitellum in a way that it does not interfere with the radial head. The plate is secured using only the most proximal holes, while the distal portion is not fixed and helps neutralize the shear forces across the fracture site [ 19 , 25 , 71 ]. There is only one clinical study on this technique.…”
Section: Treatment Options and Resultsmentioning
confidence: 99%
“…There is only one clinical study on this technique. Song et al [ 71 ] recently retrospectively reported on their case series of 52 patients, among whom, after a 17.6-month follow-up, 36 were scored excellent, 11 good, and five with fair results, according to the Mayo Elbow Performance Score (MEPS). All fractures were united by a one-year follow-up and three cases sustained hardware loosening or breakage without secondary fracture displacement.…”
Section: Treatment Options and Resultsmentioning
confidence: 99%